Hydrogen sulfide donor sodium hydrosulfide-induced heat tolerance in tobacco (Nicotiana tabacum L) suspension cultured cells and involvement of Ca(2+) and calmodulin - Li, Zhong-Guang (Plant science : an international journal of experimental plant biology, 2012)
Copyright © 2011 Elsevier Ireland Ltd. All rights reserved.